2018
DOI: 10.1080/07448481.2018.1462815
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to resistance training among college-aged women

Abstract: A majority of college-aged women are not meeting RT recommendations. Providing educational programs and avenues for finding same-sex RT partners may be most beneficial for overcoming common RT barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…In addition, the results showed perceived social and time/effort barriers to be the most prominent barriers for RT. These findings coincided with previous studies that have shown time/effort [10,11] and social barriers [12] to be the most frequent barriers among college-aged females. , feelings of incompetency, and low self-efficacy are the most frequent sources of social barriers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the results showed perceived social and time/effort barriers to be the most prominent barriers for RT. These findings coincided with previous studies that have shown time/effort [10,11] and social barriers [12] to be the most frequent barriers among college-aged females. , feelings of incompetency, and low self-efficacy are the most frequent sources of social barriers.…”
Section: Discussionsupporting
confidence: 92%
“…Despite these well-established benefits and national recommendations to adopt healthy RT habits early in life, more than 75% of college-aged females do not meet the current recommendations [8,9]. Furthermore, research has shown that young women have specific barriers [10][11][12] and maladaptive exercise motives [13][14][15][16] for RT limiting their participation in healthy RT behaviors. Thus, specific RT intervention efforts are warranted to lower these RT barriers in college-aged females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research, particularly older studies such as Harne and Bixby (2005) found time-effort barriers were most prevalent; however, we identified social barriers such as gender-based or social stigmas and lack of social support to be most prominent which is more consistent with newer research. (Peters et al, 2019;Burton et al, 2017;Cavill & Foster, 2018) Although these studies identified similar social barriers, this review particularly provided greater detail and understanding of why women felt uncomfortable in ST environments. In particular, being perceived as 'princesses', receiving negative comments, drawing attention, and feeling self-conscious exercising with others provided greater insight into why evaluation concerns (an individual's interest in others' opinion of them) are more common in women as shown by Salvatore and Marecek (2010).…”
Section: Fit With Previous Researchmentioning
confidence: 94%
“…Demographic determinants associated with ST participation identified by previous research include being male, increasing education, younger age, and Caucasian background, with the strongest predictors of participation being involvement in other physical activity and perceived good health (Chevan, 2008;Loustalot et al, 2013;Galuska et al, 2002). Barriers to ST in women reported by quantitative studies include time consumption, tiredness, appearing weak, silly or uncoordinated, fear of looking 'big and bulky', muscle soreness, judgement by friends, discomfort doing ST alone, around men or in crowded gyms, poor previous experience or failure, lack of knowledge of ST, level of discipline required, and desire (Peters et al, 2019;Hurley et al, 2018;Salvatore & Marecek, 2010). Motivators identified by previous research include making ST part of a routine, gaining supervision, enjoying ST, and finding ST helps with weight management and physical and mental well-being (Viljoen & Christie, 2015;Harne & Bixby, 2005).…”
Section: Introductionmentioning
confidence: 99%